Influence of Degree of Doneness on the Alpha-Gal Content of Striploins and its Relationship with Red Meat Allergy - Sara R. Hene; Jack R. Kress; Jordan T. Looper; Erin S. Beyer; Travis G. O'Quinn; Michael D. Chao (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: Alpha-Gal Syndrome (AGS) is an acquired sensitivity to galactose-alpha-1, 3-galactose (⍺-Gal) after exposure to a bite from the Lone Star Tick (Amblyomma americanum). Affected individuals can experience a range of symptoms from mild itching to potentially fatal anaphylaxis after consuming products containing mammalian tissues that contain ⍺-Gal. Little research has been done to examine the ⍺-Gal content of different products; thus, the objective of this study was to establish the ⍺-Gal content of striploin steaks cooked to varying degrees of doneness to evaluate if heat treatment reduces the ⍺-Gal content of red meat. Study Description: Ten beef striploins were collected from a Midwest beef processing plant and transported under refrigeration to the Kansas State University Meat Laboratory (n = 10). Striploins were cut into four steaks each and either left raw or cooked to medium rare (MR; 130°F), medium (MED; 140°F), or well done (WD; 160°F). Whole muscle proteins were extracted, and proteins were separated by gel electrophoresis, transferred to a polyvinylidene difluoride membrane, and tested by immunoblot against a primary anti-⍺-Gal antibody. Each gel contained a reference sample of ⍺-Gal conjugated human serum albumin with known ⍺-Gal content. Results: Striploins that were cooked to WD had the greatest ⍺-Gal concentration among all cooking treatments, followed by steaks cooked to MR and MED, while steaks that were left raw had the lowest ⍺-Gal concentration (P < 0.01). The Bottom Line: Our results are consistent with other studies, which indicated that cooking seems to concentrate ⍺-Gal glycans to a higher degree than that of the raw striploins. Further research is needed to evaluate the efficacy of other interventions to improve the care and management of AGS patients.
Keywords: red meat allergy; beef; alpha gal